Longitudinal assessment of motor function following the unilateral intrastriatal 6-hydroxydopamine lesion model in mice - Sun, Xiuping; Li, Xianglei; Zhang, Ling; Zhang, Yu; Qi, Xiaolong; Wang, Siyuan; Qin, Chuan (Frontiers in Behavioral Neuroscience, 2022)
Despite the widespread use of the unilateral striatal 6-hydroxydopamine (6-OHDA) lesion model in mice in recent years, the stability of behavioral deficits in the 6-OHDA striatal mouse model over time is not yet clear, which raises concerns about the use of this model for the assessment of the long-term therapeutic effects of a compound. In the current study, beginning 3 days after 6-OHDA injection of 4 μg and 8 μg, mice were tested at regular intervals in the cylinder test and gait analysis until 56 days post-lesion. Apomorphine-induced rotational test and rotarod test were also performed on Days 23 and 43 post-lesion , respectively. Immunohistochemistry for dopaminergic neurons stained by tyrosine hydroxylase (TH) was also performed. Our results showed that both the 4 μg and 8 μg 6-OHDA lesion groups exhibited forelimb use asymmetry with a preference for the ipsilateral (injection) side on Day 3 and until Day 21 post-lesion and did not show forelimb asymmetry from Day 28 to 56 post-lesion . The 8 μg 6-OHDA lesion group still exhibited forelimb asymmetry on Days 28 and 42 post-lesion and did not show forelimb asymmetry on Day 56 post-lesion. The gait analysis showed that the contralateral front and hind step cycles increased from Day 3 to 42 post-lesion and recovered on Day 56 post-lesion. In addition, our results displayed a dose-dependent reduction in TH+ cells and TH+ fibers and dose-dependent apomorphine-induced rotations were observed. In the rotarod test, the 8 μg 6-OHDA lesion group, but not the 4 μg group, decreased the latency to fall on the rotarod on Day 43 post-lesion. In summary, our findings indicated that unilateral striatal 6-OHDA injections of 4 μg and 8 μg induced spontaneous motor impairment in mice, which partially recovered starting on Day 28 post-lesion. The 8 μg 6-OHDA lesion group induced forced motor deficits, which were stable on Day 43 post-lesion. In addition, the rotarod test and apomorphine-induced rotational test are able to distinguish between lesions of different extents and provide useful tools for the assessment of functional recovery in studies screening novel potential therapies.